Students as partners in e-contents creation: A case study exploring student-staff partnership for learning and student engagement using digital applications for co-creation of e-learning materials - Nahar, Nurun; Cross, Duncan (International Journal for Students as Partners, 2020)
In order to enable learners to take control of their learning needs and actively contribute in their learning processes, educators can partner with students in various reciprocal student-staff partnership (SSP) settings where students can be co-creators, co-producers, curators, or co-deliverers of the curriculum. Our project, undertaken to enhance the curriculum as part of a teaching qualification, places emphasis on educators partnering with first-year undergraduate students over e-content creation within an existing module, using readily accessible digital applications in order to promote active learning in students and improve student engagement. In this case study, we evaluate the extent to which SSP, as an approach to the creation of e-learning materials using digital applications, enhanced learning and student engagement in an existing module. Our student partners perceived SSP to be an excellent platform for learning, actively engaging in the classroom, and developing skills such as communication and digital literacy. However, they expressed some concerns about overcoming the traditional hierarchies within our SSP initiative